2015
DOI: 10.1016/j.exppara.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of infectivity of neonates and adults from different rat strains to Toxoplasma gondii Prugniaud shows both variation which correlates with iNOS and Arginase-1 activity and increased susceptibility of neonates to infection

Abstract: Mouse models differ considerably from humans with regard to clinical symptoms of toxoplasmosis caused by Toxoplasma gondii and, by comparison, the rat model is more representative of this disease in humans. In the present study, we found that different strains of adult and newborn rats (Lewis, Wistar, Sprague Dawley, Brown Norway and Fischer 344) exhibited remarkable variation in the number of brain cysts following inoculation with the T.gondii Prugniaud strain. In adult rats, large numbers of cysts (1231 ± 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…The iNOS-mediated production of NO is a well-known molecular effector against pathogens in the innate immune responses of various animals, including mMSCs (9) and skeletal muscle cells (27), and also in vivo (15,30,31). However, a previous study reported that iNOS protein expression was not detectable in human MSCs (9).…”
Section: Discussionmentioning
confidence: 86%
“…The iNOS-mediated production of NO is a well-known molecular effector against pathogens in the innate immune responses of various animals, including mMSCs (9) and skeletal muscle cells (27), and also in vivo (15,30,31). However, a previous study reported that iNOS protein expression was not detectable in human MSCs (9).…”
Section: Discussionmentioning
confidence: 86%
“…3A). Therefore, for analysis of cyst-forming ability, the rat model system, based on the innate resistance of rats to T. gondii (Gao et al, 2015;Li et al, 2012), is much more useful. In comparison to the archetype II PRU strain, which itself is capable of cyst formation in certain rat strains, the Chinese strains of TgCtsd1 and TgCtxz3 produced over 200 times more cysts.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CBA/Rj mice and Fischer 344/IcoCrl rats as hosts for T . gondii has been described previously 59,60 . At 48 or 49 days post-injection, blood samples from five randomly-chosen mice and rats were taken and tested for antibody production by ELISA (see below); all were antibody-positive.…”
Section: Methodsmentioning
confidence: 99%